Financial Performance, Company Size and Dividend Payout Ratio In Banking Companies - Savira Putri Kesuma; Nurhasanah (LPPM Universitas Malikussaleh, 2022)
This study aims to analyze the effect of financial factors, Lagged Dividends, and company size on the Dividend Payout Ratio in banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The population in this study were all banking companies listed on the IDX as many as 43 companies. The sample in this study was taken using the purposive sampling method so that there were 21 companies as the research sample. This research data was obtained through the publication of the Indonesia Stock Exchange and the websites of these companies. This study used 21 samples with 5 years of research so that the total observations were 105 observations with the GMM method using the Eviews 12 application. The results of this study used a partial test (t test). Finds that Current Ratio, Return On Assets, Debt to Equity Ratio, Lagged Dividend, and Company Size variable has no significant effect on the Dividend Payout Ratio.